Work Satisfaction Levels of Music Therapists in the United States: A Mixed Methods Analysis - Meadows, Anthony; Eyre, Lillian; Gollenberg, Audra (Voices: A World Forum for Music Therapy, 2022)
This mixed methods study reports levels of work satisfaction of music therapists working in the United States. A total of 1,154 board-certified music therapists completed a 28-question survey focused on their workplace, work, and professional development experiences, along with their levels of stress, burnout, and happiness. Two open-ended questions asked respondents to reflect on their identities as music therapists. Composite work satisfaction scores were subsequently divided into quartiles, characterizing high, moderate, and low work satisfaction groups. Music therapists reporting high work satisfaction indicated significantly higher levels of positive agreement with questions regarding work satisfaction than did music therapists reporting moderate or low work satisfaction. Work satisfaction was also significantly associated with stress, burnout, and happiness. The profiles of music therapists reporting high, moderate, and low work satisfaction were further connected to their identities as music therapists, illuminating the characteristics of music therapists who are thriving, those who are moderately satisfied at work, and those who are struggling. These profiles provide insights into the occupational wellbeing of the profession.